Metabolic Syndrome Predicts Response to Neoadjuvant Chemotherapy in Breast Cancer - Lu, Ying; Wang, Pinxiu; Lan, Ning; Kong, Fei; Abdumijit, Awaguli; Tu, Shiyan; Li, Yanting; Yuan, Wenzhen (Frontiers in Oncology, 2022)
Purpose This research investigated the predictive role of metabolic syndrome (MetS) in breast cancer neoadjuvant chemotherapy (BCNACT) response. Methods One hundred fifty primary breast cancer (BC) patients who underwent neoadjuvant chemotherapy (NACT) were included retrospectively. MetS, MetS components [waist circumference (WC), fasting blood glucose (FBG), blood pressure, triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C)], serum lipid, and other MetS-related laboratory indicators within two weeks before BCNACT were evaluated. Univariate, multivariate, and subgroup analyses were performed to determine the predictors of BCNACT pathologic complete response (pCR), clinical response, and pathologic response. The effectiveness of the model was evaluated via receiver operating characteristic curve (ROC) and calibration curve. External validation was performed through 135 patients. Results Univariate analysis revealed that MetS before BCNACT predicted poor BCNACT response (pCR, P = 0.003; clinical response, P = 0.033; pathologic response, P < 0.001). Multivariate analysis confirmed that MetS before BCNACT predicted lower pCR rate (P = 0.041). Subgroup analysis showed that this relationship was significant in estrogen receptor (ER) (−) (RR = 0.266; 95% CI, 0.074–0.954), human epidermal growth factor 2 (HER2) (−) (RR = 0.833; 95% CI, 0.740–0.939) and TNBC (RR = 0.833; 95% CI, 0.636–0.995). Multivariate analysis of external validation confirmed that pretreatment MetS was associated with a lower pCR rate (P = 0.003), and subgroup analysis also confirmed that this relationship had significant statistical differences in ER (−), HER2 (−), and TNBC subgroups. Conclusions MetS before BCNACT predicted a lower pCR rate. Intervention on MetS status, especially in ER (−), HER2 (−), and TNBC subgroups, is expected to improve the response rate of BCNACT further.